(untitled) (Intent Research Scientific Journal, 2023)
Traffic congestion is a significant challenge in urban areas, leading to increased travel times, fuel consumption, and environmental pollution. To address this issue, researchers have developed various traffic flow distribution methods based on mathematical models. One such method involves utilizing a system of 14 differential equations to optimize traffic flow distribution. In this article, we will explore the concept behind this method and its potential applications in traffic management.